MICRO MORPHOLOGICAL CHARACTERIZATION OF MURDANNIA SPECIES - KULBHUSHAN.W. PAWAR; S.A. PATIL; SANKET P. GAWALI; SOMNATH S. SHINDE; D.D. AHIRE (The Bioscan, 2025)
The study of micro-morphological characterization, which involves examining the microscopic features of plant parts, is essential for accurate species identification and key preparation, especially in taxonomically complex groups like Murdannia. Given this background, Murdannia species were collected and maintained in a botanical garden for further study. A proper herbarium specimen was identified using a standard reference book and the Flora of Maharashtra (1996). Micro-morphological characterization of 4 different species of Murdannia–viz. Murdannia gigantea (Vahl) G. Bruckn, Murdannia lanuginosa (Wall.) G. Bruckn, Murdannia Nudiflora (L.) Brenan, and Murdannia semiteres (Dalzell) Santapau were done based on different external characters and flower morphology. using SPSS V.20, conducted a correlation (dissimilarity matrix - Euclidean Distance) between 4 different species of Murdannia. Correlation shows how the Murdannia species are near to each other or vary from each other based on morphology. This study will help the researchers identify the correct species of Murdannia. The proximity matrix shows the difference between the four species.